Independence Corrupted: How America's Judges Make Their Decisions - Schudson, Charles Benjamin (University of Wisconsin Press, 2018)
Intro -- Contents -- Preface: Sacred Words -- Introduction. Independence and Corruption -- Part One. Judges -- 1. Who's the Judge? -- 2. The Prosecutor's Perspective -- 3. The Decision-Making Ideal -- Part Two. In Chambers -- 4. The Trial Judge: Birth, Aborted -- 5. The Appellate Judge: Birth, Premature -- 6. Standard of Review: Casting the Legal Drama -- 7. The Trial Judge: Life, and a Lost Teenager -- 8. The Appellate Judge: Life, and a Sex Predator -- 9. The Trial Judge: Death, and a Cherished Child -- 10. The Appellate Judge: Death, and Three Widows -- 11. The Trial Judge: Religion, and White Supremacists -- 12. The Appellate Judge: Politics, "Out on the Point" -- 13. Indigestion: Food, Mood, and More -- Part Three. Vanishing Independence -- 14. Judicial Campaigns: Declarations and Contributions -- 15. Begging the Question: Elective or Appointive? -- Afterword. Fathers and Grandfathers -- Acknowledgments -- Notes -- Index